2022
DOI: 10.1007/s12155-022-10392-7
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Energy in Malaysia: Current Scenario, Policies, and Implementation Challenges

Abstract: The energy demand in Malaysia has shown a dramatic increase over the last few years: with natural gas and coal being the primary contributors. Nevertheless, due to declining in fossil fuel reserves coupled with negative environmental impacts, shifting to sustainable renewable energy for meeting the future energy demand is recommended. Since Malaysia is rich with natural resources, utilization of biomass energy (bioenergy/biofuel) as the alternative energy is promising to be further explored. Therefore, this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 100 publications
0
23
0
Order By: Relevance
“… Import Dependence : The absence of local manufacturers for efficient high-pressure steam generators necessitates the import of equipment required for biomass-based power generation and CHP systems [ 15 ]. It is also reported that the technologies for biogas production in Malaysia through the anaerobic digestion technique have been imported from the Germany [ 37 ]. Infrastructure Constraint : Limited access to the necessary infrastructure, such as grid connectivity and transportation networks, hinders the export of excess energy and bio-products generated from the technologies, reducing the potential benefits.…”
Section: Opportunities and Challenges For Net-zero Statusmentioning
confidence: 99%
“… Import Dependence : The absence of local manufacturers for efficient high-pressure steam generators necessitates the import of equipment required for biomass-based power generation and CHP systems [ 15 ]. It is also reported that the technologies for biogas production in Malaysia through the anaerobic digestion technique have been imported from the Germany [ 37 ]. Infrastructure Constraint : Limited access to the necessary infrastructure, such as grid connectivity and transportation networks, hinders the export of excess energy and bio-products generated from the technologies, reducing the potential benefits.…”
Section: Opportunities and Challenges For Net-zero Statusmentioning
confidence: 99%
“…The United States is currently the largest producer of biomass energy, with a total installed capacity of over 16 GW and an annual production of over 160 TWh [44]. Other countries with signi cant biomass energy production include China, India, Brazil, Germany, and the United Kingdom [45]. Bioenergy is particularly important in many developing countries where traditional biomass (e.g.…”
Section: Biomass Energymentioning
confidence: 99%
“…Due to its social and economic dimensions, the idea that urban wastes have an energy value and that biomass resources should be converted into energy is a fact that is valued and supported by many developed countries (Sergey et al, 2017). Countries are in an effort to increase their energy resources, to search for alternative energy resources and to use potential energy resources and to control prices (Rashidi et al, 2022). Countries such as Austria, Germany and Sweden have established a market dominance in their regions for using biomass energy and have opened up to pellet markets outside Europe (IRENA, 2019).…”
Section: Introductionmentioning
confidence: 99%